MRI as the Only Pre-Operative Imaging Modality in ARM: What Advantage does it Provide? - Antony Augustine; Hemonta K Dutta; Deb K Boruah; Rudra K Gogoi (EL-Med-Pub, 2017)
Background: MRI has not been traditionally used as an imaging modality for preoperative evaluation of ARM. It has been reserved for complicated ARM cases and Imaging in post-operative period. Aims: To study the role of MRI in preoperative evaluation of ARM patients, whether it be used as a single preoperative imaging investigation in ARM and what added advantage does it give to conventional imaging techniques. Settings and Design: Hospital based observational study was conducted over a period of 1 year which included 26 ARM patients who required preoperative imaging which was done using MRI. Methods and Material: Multi-planar T1 and T2WI images of pelvis were acquired followed by screening of abdomen done with coronal T2WI and screening of spine with T2FS sagittal images. Further sequences were acquired for evaluation of any target lesions as and when required. Images were evaluated for level of atresia, type of Fistula, additional anomalies in Vertebral / Spinal cord / Genital / Urinary system and sphincter muscle complex (SMC) development. Results were analysed using numbers, percentage and arithmetic mean. Results: MRI correctly identified the level of termination of rectal pouch in all patients. MRI correctly depicted the fistula in 89% cases. Seventy three percent cases had additional anomalies with 66% of cases with additional anomalies having multiple anomalies. MRI accurately evaluated SMC development in all cases. Conclusions: MRI provided elaborate pelvic anatomical details, precise information about the degree of development of pelvic musculature and information regarding the presence of additional anomalies in genitourinary and vertebra-spinal systems in a single sitting and without use of any ionizing radiation to child. We recommend MRI as the only needed imaging investigation in ARM cases before definitive surgical repair.